Pengembangan Media Vennify Untuk Pembelajaran FPB dan KPK di Sekolah Dasar - Azkiya, Nida; Arifin, Fatkhul (Jurnal keilmuan dan Kependidikan dasar, 2025)
This study aims to develop an interactive learning media called Vennify for teaching Greatest Common Factor (GCF) and Least Common Multiple (LCM), as well as to assess its feasibility and effectiveness in enhancing the conceptual understanding of mathematics among fifth-grade students at SDN Jurang Mangu Timur 02. The research employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments included validation questionnaires from media experts, subject matter experts, field practitioners, and conceptual understanding tests administered to students. The research findings indicate that the Vennify media received a feasibility score of 100% from the media expert (categorized as “Highly Feasible”), 78% from the subject matter expert (“Feasible”), and 100% from the field practitioner (“Highly Feasible”). A field trial was conducted involving 26 fifth-grade students, which revealed a significant improvement in their conceptual understanding of mathematics. This was evidenced by an increase in the average pre-test score of 59.49% to a post-test average of 82%. Based on these results, Vennify is deemed feasible and effective to be used as an alternative learning media to support the improvement of elementary students’ mathematical concept comprehension.